Color‐Customizable, Stretchable, Self‐Healable and Degradable Ionic Gel for Variable Human‐Motion Detection via Strain, Pressure, and Torsion. Issue 11 (12th February 2022) - Wang, Peng; Li, Guoxian; Yu, Wei; Meng, Chuizhou; Guo, Shijie
Abstract: Recently, flexible sensors have attracted great interest for their promising application in wearable electronics. However, previous mechanical sensors are typically limited to detecting one type of stimulus and monotonous in color, which are not able to meet the sensing nor fashion requirements by customers who will wear them in daily life. Herein, a flexible and stretchable sensor based on highly conductive ionic gel is developed. Different phosphor nanoparticles are uniformly embedded into gel to enable color‐customization and even self‐illumination depending on preference. The gel is also self‐healable after complete severance and degradable in hot water. The sensors can detect multiple mechanical deformation modes to allow for detections of strain, pressure, and torsion on a single device. Wearable sensing prototypes are demonstrated with attachment to different parts of human body to detect various human motions, including strain sensing for frowning and elbow/knee bending, pressure sensing for vocal cord vibrations and pulse at wrist, and torsion sensing for shoulder and forearm rotations, through an in‐house, wireless, real‐time signal transmission and process system. Considering its sensing capability toward different stimuli as well as superior physical properties, the developed color‐customizable and self‐illuminating ionic gel sensor would find its promising applications toward wearable sensing. Abstract : A flexible and stretchable ionic gel is developed. It is not only color‐customizable and self‐illuminating, but also self‐healable after complete severance and easily degradable in hot water. Sensors based on the ionic gel can be used for detecting various types of human‐motions, including strain, pressure, and torsion. Correspondingly, wearable sensors are demonstrated with attachment to different parts of human body.